German National Reports on the 20th International Congress of Comparative Law - Schmidt-Kessel, Martin (Rechtsvergleichung und Rechtsvereinheitlichung, 2018)
Der 20. Internationale Kongreß für Rechtsvergleichung findet im Juli 2018 im japanischen Fukuoka statt. Auch die deutsche Rechtsvergleichungswissenschaft liefert Länderberichte. Der Band bildet dabei das gesamte Spektrum des Rechts durch die von der Internationalen Akademie für Rechtsvergleichung vorgegebenen Einzelthemen ab. Die Themen reichen von Multikulturalität über Fragen der Sprache, die Arzthaftung, die Kontrolle von Preisvereinbarungen, den Schutz der Kommunikation zwischen Verteidiger und Angeklagtem bis hin zu Datenschutz und Klimawandel.InhaltsübersichtTable of Contents: Jan Thiessen: Comparative Law and Multicultural Legal Classes: Challenge or Opportunity? A legal-historical account from Germany – Johanna Croon-Gestefeld: Property Meeting the Challenge of the Commons – Katharina Erler/Martin Schmidt-Kessel: The Use of the UPICC in Order to Interpret or Supplement German Contract Law – Stefan Grundmann: Language in Law and in German Universities' Legal Education – Anne Sanders: Conditions of the Recognition of the Civil Status of Transsexual and Transgender People – Andreas Spickhoff: Legal Questions concerning Medical Malpractice Liability: Substantive Law and its Enforcement – Anatol Dutta: Multicultural Challenges in German Family Law – Boris Schinkels: Information/Disinformation of Consumers Including Negotiation – Matthias Weller: Optional Choice of Court Agreements – Marc-Philippe Weller/Leonhard Hübner/Luca Kaller: Private International Law for Corporate Social Responsibility – Wolfgang Hau: Anti-Suit Injunctions in Judical and Arbitral Procedures – Matthias Fervers/Beate Gsell: Control of Price Related Terms in Standard Form Contracts – Sebastian Mock: Groups of Companies – Les groups de sociétés – Tobias H. Tröger: Regulation of Crowdfunding – Moritz Brinkmann/David Rüther/Bianca Scraback: Security Rights in Intellectual Property – Klaus Tonner: Legal Aspects of Cruises – Stefanie Schmahl: The Fight against Poverty and the Right to Development in the German Legal Order – Lars Viellechner: »Friendliness« towards Others: How the German Constitution Deals with Legal Pluralism – Jürgen Kühling: The Right to Be Forgotten – Bettina Weisser: Confidentiality of Correspondence with Counsel as a Requirement of a Fair Trial – Christina Breunig /Martin Schmidt-Kessel: Data Protection in the Internet – Joachim Münch: Legal Professions and the Transfer of Real Estate – Dirk Hanschel: Climate Change and the Individual